Integrated care partnerships in Northern Ireland: added value or added bureaucracy?. Issue 5 (15th December 2014) - Birrell, Derek; Heenan, Deirdre
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore and assess the configuration, role and likely contribution of the new integrated care partnerships (ICPs) established in Northern Ireland. Design/methodology/approach – The approach is based on the assessment of policy background, strategy papers, implementation plans and initial activities of ICPs. Findings – ICPs have been created with limited powers and an unclear relationship with the existing system of structurally integrated health and social care. The initial priorities and activities of ICPs suggest a focus on integrating health which may impede the further integration of health and social care. Research limitations/implications – Paper concludes there is a need for robust evaluation including monitoring of progress, performance and outcomes. Originality/value – First published paper on implementation of ICPs in Northern Ireland. Contributing to comparative studies of structures of health and social care, with particular relevance to integration.